Analisis Fundamental Cryptocurrency terhadap Fluktuasi Harga: Studi Kasus Tahun 2019-2020 - Septiana Sihombing; Muhammad Rizky Nasution; Isfenti Sadalia (Penerbit Goodwood, 2021)
Purpose: This study aimed to analyze cryptocurrency fundamentals against price fluctuations (case study 2019-2020). Research Methodology: The data in the research paper were accessed on the coinmarketcap.com website. The sample of this research is Bitcoin, Ethereum, Litecoin, and Bitcoin Cash. Results: The results show that: 1) Bitcoin Market Cap, Ethereum Market Cap, Litecoin Market Cap, Bitcoin Cash Market Cap have a positive and significant effect on price fluctuations. 2) Bitcoin Volume and Bitcoin Cash Volume have a positive and insignificant effect on price fluctuations. 3) Ethereum volume has a positive and significant effect on price fluctuations. 4) Litecoin volume has a negative and significant effect on price fluctuations. Limitations: Further researchers are expected to add variables such as (global macroeconomics, cryptocurrency Blockchain technology changes, psychological factors), different variables (quantitative and qualitative) and combine models to predict cryptocurrency price fluctuations by analyzing them fundamentally and technically. Contribution: This research implies that cryptocurrencies with highly speculative prices have the same fundamental value as the stock price.